LOCALLY SMALL RIEMANN SUMS FUNGSI TERINTEGRAL HENSTOCK-DUNFORD PADA RUANG EUCLIDE - Solikhin, Solikhin (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
In this paper we study Henstock-Dunford integral on the Euclidean space . We discuss some properties of the integrable. We shall define locally small Riemann sums (LSRS) andÂ show that it is necessary and sufficient condition for function to be Henstock-Dunford integral on the Euclidean space . Â Kata Kunci : Henstock-Dunford integral, Locally small Riemann sums